Development of MOOCs in Civil Engineering Education through Gamification Implementation - Reza Aprilianto Mandala Putra; Anisah Anisah; Tuti Iriani (Jurnal Pendidikan Teknik Sipil, 2023)
Background: Massive Open Online Courses (MOOCs) represent an accessible online learning platform open to everyone without specific conditions. The prominence of MOOCs has surged, particularly following the Covid-19 pandemic. Despite this global trend, the development of MOOCs in Indonesia faces challenges such as community unpreparedness and inadequate infrastructure. Traditional education perceptions persist, with many Indonesians believing in the necessity of formal education. Gamification, involving the incorporation of enjoyable and engaging game elements into non-game activities, presents an innovative approach. Given the relatively low demand for MOOCs in Indonesia, gamification is employed to enhance user motivation and retention, with the expectation of increasing student interest in utilizing MOOCs.Methods: The research methodology employed is Research and Development (R&D), utilizing the Four D-Models model and gamification analysis through the Octa lysis Gamification Framework. This framework serves as the foundation for the selection of gamification elements.Results: Media validation results demonstrate an 86% feasibility rating for gamification-based MOOC products in Engineering Mechanics 1 courses, categorizing it as "Very Decent." Overall, the MOOC platform achieves a 92% feasibility rating, also falling into the "Very Decent" category.Conclusion: In conclusion, the research affirms that the development of gamification-based MOOCs in Engineering Mechanics 1 courses is viable for integration into the learning process. This is supported by the positive results from media validation and trials, both categorized as "Very Decent."